Professionals' perceptions of the establishment of a specialized brief therapy unit in a district psychiatric centre - a qualitative study - Hilde V. Markussen; Lene Aasdahl; Marit B. Rise (BMC, 2020)
Abstract Background Increasing mental health problems and scarce treatment resources put pressure on mental health services to make innovations in service provision, such as developing differentiated services adapted to different needs. One innovation in differentiated service provision is brief or short-term treatment to patients with moderate mental health problems. Implementing a new unit in an organization usually faces many potential barriers and facilitators, and knowledge on how the professionals providing the services perceive the implementation of innovative approaches in mental health services is scarce. The aim of this study was therefore to explore the professionals' perceptions of how the establishment of a specialized brief therapy unit had affected the organization, especially the everyday work in the outpatient clinics. Methods Eleven professionals, five men and six women, took part in individual interviews. All participants were between 40 and 60 years old and had leading or coordinating positions in the organization. Their professional backgrounds were within psychology, nursing and medicine, most of them specialists in their field. Data was analyzed according to Systematic text condensation. Results The professionals' experiences represented four main themes: (1) The brief therapy unit was perceived as successful and celebrated. (2) The general outpatient clinics, on the other hand, were described as "forgotten". (3) The establishment process had elucidated different views on treatment in the outpatient clinics - and had set off (4) a discussion regarding the criteria for prioritizing in mental health services. Conclusion Providing targeted treatment to patients with moderate mental health problems, while having a concurrent aim to solve broader problems in mental health services, entails a discussion regarding resource use and the appropriate level of treatment provision. Professionals should be more involved when innovative efforts are implemented, and the criteria for success must be conceptualized and evaluated. Longitudinal research on the implementation of innovative efforts in the services should include professionals' and service users' perspectives.